Comparison of a retraction exercise and passive scapular lifting for acute scapular medial pain - Yoo, Won-gyu (Journal of Physical Therapy Science, 2018)
[Purpose] This study developed an effective self-relaxation exercise for acute scapular medial pain and investigated its pain relief effects. [Subject and Methods] The subject was a 41-year-old male with scapular medial pain. During session 1, the subject performed a retraction exercise. During session 2, the subject performed a passive scapular lifting exercise. [Results] After session 2, the frequency of the pain decreased to about once a month, and the patient’s VAS score for acute scapular medial pain was 2/10. After session 1, there was no change compared to the initial values. [Conclusion] Therefore, the results of this study suggest that the passive scapular lifting exercise offers effective control of acute scapular medial pain.